1938
DOI: 10.1002/jcp.1030120306
|View full text |Cite
|
Sign up to set email alerts
|

Creatine in nerve, muscle and brain

Abstract: ONE FIGUKEEarlier experiments on soluble phosphates in frog nerve (Gerard and Wallen, '29) showed the presence of a fraction, 'labile phosphate,' closely resembling in behavior the phosphagen or creatine-phosphate of muscle. A similar arginine-phosphate fraction has been studied in invertebrate nerve (Tang, Tang and Gerard, '32 ; Engel and Gerard, '35). The more complete identification of the nerve substance could be achieved by actual isolation, a rather thankless task when but a few milligrams of nerve are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1939
1939
1965
1965

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Basically similar results to the present ones were obtained by Gerard & Tupikova (1938, 1939. They observed that during stimulation of sciatic nerve the Pi content was elevated.…”
Section: Phosphorus Metabolism Of Nerve 409supporting
confidence: 92%
“…Basically similar results to the present ones were obtained by Gerard & Tupikova (1938, 1939. They observed that during stimulation of sciatic nerve the Pi content was elevated.…”
Section: Phosphorus Metabolism Of Nerve 409supporting
confidence: 92%
“…The energy reserve represented by creatlne phosphate and ATP may be computed to be 0.19 cal./gm, dry, if one uses the estimates of Gerard and Tupikova (1938) and Greengard et al (1954) for the nerve content of these substances and employs the previous figure for the free energy of hydrolysis of the terminal phosphate bonds of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the free energy required to transport sodium and potassium ions comprises approximately 10 per cent of that available from the metabolism in oxygen and about one-third of that II Calculated assuming free energy of hydrolysis of the terminal phosphate group of ATP and creatine phosphate to be -8 kcal./mole (Kitzinger et od., 1957). ¶ Gerard and Tupikova (1938). **Greengard, Brink, and Colowick (1954).…”
Section: Wn = Rt In [Na°~ ~Nal] -I-fe/jmentioning
confidence: 99%